2021
DOI: 10.1029/2020jf005696
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of the Snowmelt‐Albedo Feedback in Antarctica

Abstract: Surface melt is an important process for the stability of ice shelves, and therewith the Antarctic ice sheet. In Antarctica, absorption of solar radiation is mostly the largest energy source for surface melt, which is further enhanced by the snowmelt‐albedo feedback (SMAF): Refrozen snow has a lower albedo than new snow, which causes it to absorb more solar radiation, further increasing the energy available for surface melt. This feedback has previously been shown to increase surface melt by approximately a fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…This is supported by the statistically significant positive correlation of MLT of OH-12 with ERA5 near-surface air temperatures at the site (r = 0.5, p < 0.0001; Table 5). In addition, increased insolation on cloud-free days and hence the absorption of solar radiation by the snowpack can further trigger surface melt [100]. However, due to the exposed position of the study site, high wind speeds may occur year-round (Supplementary Figure S4).…”
Section: Relation Between Firn Core and Meteorological Recordsmentioning
confidence: 99%
“…This is supported by the statistically significant positive correlation of MLT of OH-12 with ERA5 near-surface air temperatures at the site (r = 0.5, p < 0.0001; Table 5). In addition, increased insolation on cloud-free days and hence the absorption of solar radiation by the snowpack can further trigger surface melt [100]. However, due to the exposed position of the study site, high wind speeds may occur year-round (Supplementary Figure S4).…”
Section: Relation Between Firn Core and Meteorological Recordsmentioning
confidence: 99%
“…This overestimation is mainly caused by the high temperature sensitivity of the PDD model and is amplified by our treatment of the monthly mean temperature inputs at the iceatmosphere interface. Because the PDD model is tuned in a way that all surface melt is caused by temperatures only -which is in contrast to in situ observations showing that in the cold Antarctic climate, insolation is usually the predominant energy source for melt at the surface (Jonsell et al, 2012;King et al, 2015;Broeke et al, 2005b;Jakobs et al, 2020Jakobs et al, , 2021 cf. also Fig.…”
Section: Uncertainty Estimation Of Predicted 21 St -Century Surface Meltmentioning
confidence: 99%
“…Especially the changes in snow grain sizes, e.g., due to snow aging, are an important factor that is neglected in the model but plays a major role for the albedo. While snow aging generally leads to a reduction in albedo, and its neglect should therefore in principle lead to an underestimation of melt rates at the end of the melt season, there are important processes that act in the opposite direction: a major caveat of the scheme is that it neglects the influence of changes in snow cover thickness that could mitigate the melt-induced reduction in albedo after heavy snowfall events or inhibit the melt-albedo feedback (Picard et al, 2012;Jakobs et al, 2021). However, on the long timescales considered here individual snowfall events are likely to only play a minor role as compared to the mean surface conditions.…”
Section: Uncertainty Estimation Of Predicted 21 St -Century Surface Meltmentioning
confidence: 99%
See 1 more Smart Citation
“…Snowpack is a crucial component of the cryosphere, serving as a huge water reservoir for river catchments, and it is especially important for the regional sustainability of ecosystems and communities (Barnett et al., 2005; Hugonnet et al., 2021; Sturm et al., 2017). The surface energy budget of snow‐covered regions, and the ablation rate of the snowpack in particular, are significantly affected by snow albedo (Flanner et al., 2011; Jakobs et al., 2021; Riihelä et al., 2021; Zhang et al., 2021). Numerous observations and model simulations have shown that light‐absorbing particles (LAPs; e.g., black carbon (BC) and mineral dust (hereafter referred to as dust)) within the snowpack can reduce snow albedo and accelerate snow melting by enhancing the absorption of solar radiation (Chylek et al., 1983; Dumont et al., 2020; Hadley & Kirchstetter, 2012; Liou et al., 2014; Shi et al., 2020; Skiles & Painter, 2019), which has important implications for regional climate, hydrology, and ecological systems (Hansen & Nazarenko, 2004; Matt et al., 2018; Oaida et al., 2015; Qian et al., 2011; Yasunari et al., 2012).…”
Section: Introductionmentioning
confidence: 99%